eHealth literacy was associated with anxiety and depression during the COVID-19 pandemic in Nigeria: a cross-sectional study - Akingbade, Oluwadamilare; Adeleye, Khadijat; Fadodun, Oluwadamilola Agnes; Fawole, Israel Opeyemi; Li, Jiaying; Choi, Edmond Pui Hang; Ho, Mandy; Lok, Kris Yuet Wan; Wong, Janet Yuen Ha; Fong, Daniel Yee Tak; Ogungbe, Oluwabunmi (Frontiers in Public Health, 2023)
Background Electronic health (eHealth) literacy may play an important role in individuals’ engagement with online mental health-related information. Aim To examine associations between eHealth literacy and psychological outcomes among Nigerians during the Coronavirus disease-2019 (COVID-19) pandemic. Methods This was a cross-sectional study among Nigerians conducted using the ‘COVID-19’s impAct on feaR and hEalth (CARE) questionnaire. The exposure: eHealth literacy, was assessed using the eHealth literacy scale, and psychological outcomes were assessed using the PHQ-4 scale, which measured anxiety and depression; and the fear scale to measure fear of COVID-19. We fitted logistic regression models to assess the association of eHealth literacy with anxiety, depression, and fear, adjusting for covariates. We included interaction terms to assess for age, gender, and regional differences. We also assessed participants’ endorsement of strategies for future pandemic preparedness. Results This study involved 590 participants, of which 56% were female, and 38% were 30 years or older. About 83% reported high eHealth literacy, and 55% reported anxiety or depression. High eHealth literacy was associated with a 66% lower likelihood of anxiety (adjusted odds ratio aOR, 0·34; 95% confidence interval, 0·20–0·54) and depression (aOR: 0·34; 95% CI, 0·21–0·56). There were age, gender, and regional differences in the associations between eHealth literacy and psychological outcomes. eHealth-related strategies such as medicine delivery, receiving health information through text messaging, and online courses were highlighted as important for future pandemic preparedness. Conclusion Considering that mental health and psychological care services are severely lacking in Nigeria, digital health information sources present an opportunity to improve access and delivery of mental health services. The different associations of e-health literacy with psychological well-being between age, gender, and geographic region highlight the urgent need for targeted interventions for vulnerable populations. Policymakers must prioritize digitally backed interventions, such as medicine delivery and health information dissemination through text messaging, to address these disparities and promote equitable mental well-being.